Pengaruh Teknik Penyuluhan Terhadap Keikutsertaan Pemeriksaan IVA Pada WUS Di Kelurahan Dasan Agung Kota Mataram Nusa Tenggara Barat - Mutiara Rachmawati Suseno; Rosita Wati; Yunita Marliana (Poltekkes Kemenkes Mataram, 2019)
Background and purpose: nationally the implementation of early detection program with IVA examination method simultaneously in all regions in Indonesia conducted on 21 April 2015 with efforts to reduce the incidence of ca cervical in Indonesia. In Puskesmas Dasan Agung, IVA examination program started in 2016 with the lowest presentation among all health centers in Mataram city that is much as (1,39%) with the number of WUS 4153 soul and who come check as many as 58 people. This study aims to determine the influence of extension techniques on the participation of IVA examination in WUS in Kelurahan Dasan Agung. Methods: This research uses Quasi Experiment research design. The population in this study were all women of childbearing age in Kelurahan Dasan Agung as many as 2462 peoples. Samples in research using purposive sampling technique counted 60 peoples. The analysis used chi-square test. Results: From 60 respondents, who participated in IVA examination in the intervention group with 17 lectures (56,7%) interactive lecture and control group with lecture counseling technique as many as 4 people (13,3%). Chi-square analysis results obtained there is influence of extension technique to IVA examination involvement with obtained value p value = 0,001 atau p < α=0,05. Conclusion: extension techniques have an effect on the participation of IVA examination in WUS in Kelurahan Dasan Agung.